1993
DOI: 10.1095/biolreprod49.6.1353
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-Cadherin in Immature Rat and Mouse Testis and in Rat Sertoli Cell Cultures1

Abstract: Cadherins are Ca(2+)-dependent cell adhesion molecules that play essential roles in organogenesis. Northern blot analysis was used to determine the levels of epithelial (E)-, neural (N)-, and placental (P)-cadherin expression in developing rat testes from 1-, 2-, 3-, and 4-wk-old rats. Highest expression of all three cadherins occurred during the first two postnatal weeks, prior to the establishment of the blood-testis barrier. Transcripts of all three cadherins were also detected in RNA isolated from Sertoli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
1
51
0
3
Order By: Relevance
“…In the testis, Sertoli and germ cells have been shown to express both E-and N-cadherin (Wu et al, 1993;Lee et al, 2003), but the expression of E-cadherin by germ cells was considerably higher than that of N-cadherin . In addition, E-cadherin expression in undifferentiated type A spermatogonia was recently demonstrated in the mouse testis (Tokuda et al, 2007), which clearly illustrates that spermatogonia use this cell adhesion protein predominantly to adhere to Sertoli cells.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
“…In the testis, Sertoli and germ cells have been shown to express both E-and N-cadherin (Wu et al, 1993;Lee et al, 2003), but the expression of E-cadherin by germ cells was considerably higher than that of N-cadherin . In addition, E-cadherin expression in undifferentiated type A spermatogonia was recently demonstrated in the mouse testis (Tokuda et al, 2007), which clearly illustrates that spermatogonia use this cell adhesion protein predominantly to adhere to Sertoli cells.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
“…The dramatic reduction of these transporters was also seen in the corpus and cauda epididymis (data not shown). However, levels of E-cadherin and -catenin, key molecules associated with cell adhering junctions in the blood-testis barrier (Wu et al, 1993;Wong et al, 2004), were not impaired in Gpr48 -/-reproductive tracts (see Disruption of ER and Ar expression in the epididymis of Gpr48 -/-mice NHE3 and Aqp9 expression in the male reproductive tract is under the control of estrogen signaling, whereas the Na + -K + -ATPase 1 subunit is regulated by circulating androgens (Oliveira et al, 2005;Ruz et al, 2006). As serum hormone levels are not changed in Gpr48 -/-mice, we examined ER and androgen receptor (Ar) expression in the epididymis and efferent ducts.…”
Section: Reduced Expression Of Water and Ion Transporters In Reproducmentioning
confidence: 99%
“…The dramatic reduction of these transporters was also seen in the corpus and cauda epididymis (data not shown). However, levels of E-cadherin and -catenin, key molecules associated with cell adhering junctions in the blood-testis barrier (Wu et al, 1993;Wong et al, 2004), were not impaired in Gpr48 -/-reproductive tracts (see …”
mentioning
confidence: 99%
“…This finding further strengthens the notion of this disengagement mechanism. Second, many of the proteins that were included in the studies reported here, such as cadherins (33,34), catenins (33), and JAMs (27,35), are also products of germ cells including spermatids. As such, an induction of any of these proteins during germ cell loss as detected by immunoblotting is likely an ''underestimate'' instead of an artifact of ''overestimate'' for up-regulation, because the testis lysates that were being analyzed had been contributed by Sertoli and other somatic cells (e.g., Leydig and myoid cells).…”
Section: Issues On Changes In the Localization Patterns And Levels Ofmentioning
confidence: 99%